Pengaruh Kinerja Keuangan, Leverage, Corporate Governance dan Ukuran Perusahaan terhadap Sustainability Report Perusahaan LQ 45 - Nurdin Salim; Novita W Respati; Lili Safrida (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to determine and analyze the effect of profitability, leverage, institutional ownership, audit committees, independent commissioners and company size on the sustainability reports of LQ 45 companies listed on the IDX in 2015-2019. Based on purposive sampling, there were 17 companies according to the research criteria multiplied by the number of 5 years of observation, 85 data were processed and analyzed using multiple linear regression. The results simultaneously variable profitability, leverage, institutional ownership, audit committee, independent commissioners and company size have a significant effect on sustainability reports while partial testing shows that only audit committees have a significant effect on sustainability reports.